Three economist's tools for antitrust and merger analysis: Case applications - Russell W. Pittman (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2021)
This paper presents a non-technical introduction to three economic tools that have in recent years become widespread in competition law enforcement in general and in the analysis of proposed mergers in particular: critical loss analysis, upward pricing pressure, and the vertical arithmetic. In addition, for each tool, its use in a recent U.S. merger case is illustrated: for critical loss analysis, the Novelis/Aleris merger; for upward pricing pressure, the GE/Electrolux merger; and for the vertical arithmetic, the Comcast/NBCU joint venture.
Keywords: 330; Merger enforcement; Critical loss analysis; Upward pricing pressure; Vertical arithmetic; Horizontal mergers; Vertical mergers; Antitrust economics